油茶蒲纯化多糖的制备与组分、结构分析Preparation and component, structure analysis of purified polysaccharides from Camellia oleifera fruit hull - 舒斌斌1,2,3，吴苏喜1,2,3，谢妍祎1，袁成华2，冯宗义3SHU Binbin1,2,3, WU Suxi1,2,3, XIE Yanyi1，YUAN Chenghua2，FENG Zongyi3 (Zhongguo youzhi, 2023)
为高值化开发利用油茶蒲资源，以油茶蒲为原料，采用水提-醇沉工艺提取粗多糖，采用钠型732阳离子吸附树脂进行纯化并制备油茶蒲纯化多糖。采用紫外可见光谱扫描鉴定洗脱液组分多糖的纯度，利用离子色谱分析油茶蒲纯化多糖的单糖组成，利用红外光谱分析油茶蒲纯化多糖主链结构及官能团，并采用扫描电子显微镜分析其表面结构特征。结果表明：油茶蒲原料的多糖含量为11.38%，油茶蒲纯化多糖纯度为87.40%、得率为2.33%； 油茶蒲纯化多糖的单糖组成为岩藻糖0.64%、阿拉伯糖7.68%、半乳糖3.74%、葡萄糖76.43%、木糖2.77%、甘露糖1.60%、半乳糖醛酸5.34%、葡萄糖醛酸1.33%、甘露糖醛酸0.47%；油茶蒲纯化多糖是一种主链为β型吡喃糖的酸性多糖，表面紧致略显光滑、有孔洞及气泡状颗粒。综上，油茶蒲通过水提、醇沉和柱层析纯化处理，其多糖纯度提高，可为油茶蒲的后续构效关系探究和工业化开发提供理论基础。 In order to develop and utilize Camellia oleifera fruit hull resources with high value, the crude polysaccharide was extracted by water extraction-alcohol precipitation process with Camellia oleifera fruit hull as raw material, and it was purified by sodium type 732 cation adsorption resin to obtain purified polysaccharide of Camellia oleifera fruit hull. The purity of the eluent component polysaccharide was determined by ultraviolet spectroscopy, the monosaccharide composition of purified polysaccharide of Camellia oleifera fruit hull was analyzed by ion chromatography, the main chain structure and functional groups of the purified polysaccharide was analyzed by infrared spectroscopy, and the surface structure characteristics of the purified polysaccharide was analyzed by scanning electron microscopy. The results showed that the polysaccharide content of Camellia oleifera fruit hull was 11.38%. The purity of purified polysaccharide of Camellia oleifera fruit hull was 87.40% and the yield was 2.33%. The monosaccharide composition of the purified polysaccharide of Camellia oleifera fruit hull was fucose 0.64%, arabinose 7.68%, galactose 3.74%, glucose 76.43%, xylose 2.77%, mannose 1.60%, galacturonic acid 5.34%, glucuronic acid 1.33%, and mannuronic acid 0.47%. The purified polysaccharide obtained from Camellia oleifera fruit hull was a kind of acidic polysaccharide with β -type pyranose as main chain, and its surface was tight and slightly smooth with holes and bubble particles. In summary, after water extraction, alcohol precipitation and column chromatography purification, the polysaccharide purity of Camellia oleifera fruit hull gradually increased, which could provide a theoretical basis for the follow-up structure-activity relationship exploration and industrial development of Camellia oleifera fruit hull.